PTU-181 Relationship Between Barrett's Oesophagus And Abdominal Adiposity Or Bmi And Activated Pathways In Progression To Cancer. (9th June 2014) - DiCaro, S; Cheung, WH; Haidry, R; Fini, L; Keane, M; Lovat, L; Batterham, R; Banks, M
Abstract : Introduction: Barrett's oesophagus (BE) remains the strongest risk factor for oesophageal adenocarcinoma (OAC). Several studies describe an association between BE and obesity through mechanical and metabolic consequences. Visceral fat is a recognised endocrine organ. Adipokines and insulin resistance impact upon obesity-related diseases and cancer pathways. Our aims were to evaluate the relationship between BE, abdominal adiposity/BMI and pathways in the progression to cancer. Methods: Height, weight, waist-hip ratio, blood pressure assessment and fasting blood samples were obtained from sequential patients (pts), undergoing gastroscopy. BMI, fasting glucose and insulin, lipids, leptin and adiponectin were measured. Pts were then classified as normal-weight, overweight or obese and the presence of abdominal obesity (AO) and/or metabolic syndrome (MS, defined by WHO criteria) documented., to evaluate the relationship between BMI and abdominal adiposity with metabolic indices and adipokines in BE compared to controls. Biopsies were obtained from BE and histological progression to cancer was correlated with metabolic indexes. Chi square, Fisher, t-Student test and logistic analysis were used for comparison. Results: 480 patients were enrolled (250 cases: F/M: 57/193; mean age: 63.7; 230 controls: F/M: 136/94; mean age: 51.9). Metabolic derangements were more common in BE compared to controls; Metabolic syndrome (33.2 vs 20%; OR 1.95; p = 0.0017), insulin levels (10.2 vs 7.2µIU/ml; p = 0.001), HbA1c (5.8 vs 5.1%; p < 0.01), insulin resistance (47 vs 27%; OR 1.54; p < 0.01), dyslipidaemia (72.8 vs 53.9; OR 2.3; p < 0.0001) and hypertension (37.4 vs 21.3%; OR 2.4; p < 0.001). MS was present in 39.7 vs 34.2% (OR 3.05; p < 0.001), 43.7 vs 21.9% (OR 5.2; p < 0.001), 92.1 vs 54.9% (OR 8.08; p < 0.0001), in overweight, obese, AO pts with BE and controls, respectively. Insulin resistance was present in 39.2 vs 33.8% (OR 1.3; p < 0.05), 38 vs 22.3% (OR 1.7; p < 0.01) and in 82.5 vs 54.5% (OR 1.5; p < 0.001) in overweight, obese and AO pts, respectively. A trend was observed for decreased adiponectin levels in BE vs controls while leptin levels showed no correlation. In BE pts, the presence of dysplasia was associated with MS (42 vs 25%; p = 0.005) and and insulin resistance (51.4 vs 34.0%; p = 0.005). Conclusion: BE association with insulin resistance and MS suggests activation of specific metabolic pathways in pts with abdominal obesity or BMI. Progression to cancer appears driven by metabolic dysfunction in MS and a carcinogenic insulin pathway. Disclosure of Interest: None Declared.